1991
DOI: 10.1109/49.103559
|View full text |Cite
|
Sign up to set email alerts
|

Local area network characteristics, with implications for broadband network congestion management

Abstract: This paper examines the phenomenon of congestion in order to better understand the congestion management techniques that will be needed in high-speed, cell-based networks. The first step of this study is to use high time-resolution local area network (LAN) traffic data to explore the nature of LAN traffic variability. Then, we use the data for a trace-driven simulation of a connectionless service that provides LAN interconnection. The simulation allows us to characterize what congestion might look like in a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(96 citation statements)
references
References 20 publications
1
94
0
1
Order By: Relevance
“…Some studies show that the time interval between packages is not explicitly distributed. For example, the studies described in [5][6][7][8] confirm that the distribution of the time interval between the packet entries in the local and global networks differs from the exponential distribution. Therefore, the statistical "self-similar" processes, which differ from the Poisson process for their network traffic modeling, began to be used [9,10].…”
Section: Poisson Modelmentioning
confidence: 79%
“…Some studies show that the time interval between packages is not explicitly distributed. For example, the studies described in [5][6][7][8] confirm that the distribution of the time interval between the packet entries in the local and global networks differs from the exponential distribution. Therefore, the statistical "self-similar" processes, which differ from the Poisson process for their network traffic modeling, began to be used [9,10].…”
Section: Poisson Modelmentioning
confidence: 79%
“…The data distribution is depicted in Figure 6. This real-life data set has been used also in [51,66,57,36]. The statistics of the most significative data sets are reported in Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Network arrivals are often modeled as Poisson processes for analytic simplicity. However, a number of studies with the Internet traffic has shown that both local-area and wide-area network inter-arrival packet distribution clearly differs from exponential [18][19][20]. Leland et al [21], in their paper, showed that the LAN traffic is better modeled using statistically Self-Similar processes.…”
Section: Self-similar Trafficmentioning
confidence: 99%